Encyclopaedia of women in South Asia - Mittra, Sangh; Kumar, Bachchan, 1958- (Kalpaz Pub., 2004)
Encyclopaedia makes a comprehensive study of women in eight countries including India, Pakistan, Afghanistan, Sri Lanka, Bagladesh, Nepal, Bhutan and Maldives. The theme deals with historical background, geography, people of that country, their religious status, right to properties, national policy for the development of education, formal education, training of teachers, welfare of students, open schools and centres of higher education, technical education etc. Emphasis has been given on changing social status of women. Two chapters have been devoted on the role of women in politics and governmental service. They have begun participating in active politics although such a number is fairly small, on account of lack of education. India, indeed, has greatly cared for the political, and cultural development of women. In South Asia, as a whole, women are being provided with opportunities to join government service. These volumes will prove a great informative value and a regular library reference tool. Social scientists, teachers, students and other interested will find them equally useful.